2012
DOI: 10.3109/01942638.2011.652804
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of Tactile Assessments for Children with Unilateral Cerebral Palsy

Abstract: A systematic review identified tactile assessments used in children with cerebral palsy (CP), but their reproducibility is unknown. Sixteen children with unilateral CP and 31 typically developing children (TDC) were assessed 2-4 weeks apart. Test-retest percent agreements within one point for children with unilateral CP (and TDC) were Semmes-Weinstein monofilaments: 75% (90%); single-point localization: 69% (97%); static two-point discrimination: 93% (97%); and moving two-point discrimination: 87% (97%). Test-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
56
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 32 publications
4
56
0
2
Order By: Relevance
“…The ICC values were interpreted according to recommended criteria [39] previously used in studies with children [40], whereby an ICC > 0.75 was considered to be excellent, 0.74 -0.60 to be good, 0.59 -0.40 to be fair and < 0.4 to be poor.…”
Section: Discussionmentioning
confidence: 99%
“…The ICC values were interpreted according to recommended criteria [39] previously used in studies with children [40], whereby an ICC > 0.75 was considered to be excellent, 0.74 -0.60 to be good, 0.59 -0.40 to be fair and < 0.4 to be poor.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature advocates the use of familiar everyday objects in haptic object recognition assessment methodologies for children (Auld et al ., ; Yekutiel et al ., ). However, more recently studies have indicated a ceiling effect for measures of stereognosis that use common objects and suggest that novel or more complex objects are needed to reflect changes in performance over time (Auld et al ., ). None of the participants in the current study (TD or CP) achieved a maximum score on the fTORT, and variability in performance was seen across age groups.…”
Section: Discussionmentioning
confidence: 97%
“…These deficits can present bilaterally or unilaterally, and often with more than one somatosensory domain involved (e.g. proprioception and haptic object recognition) (Auld, Ware, Boyd, Moseley & Johnston, ; McLean, Taylor, Valentine, et al .).…”
Section: Introductionmentioning
confidence: 99%
“…A common choice is direct electrical median nerve stimulation 7,8 , with the potential for discomfort. Other effective methods use active tasks such as discrimination, recognition, and localization of stimuli, requiring both attention and high levels of comprehension 9 . All of these methods are therefore limited in their use in young children and infants.…”
Section: Introductionmentioning
confidence: 99%